H2O2-induced mild stress in relation with in vitro ovine oocyte developmental competence: implications for blastocyst apoptosis and related genes expression - Nikdel, K.; Aminafshar, M.; Mohammadi-Sangcheshmeh, A.; EmamJomeh-Kashan, N.; Seyedjafari, E. (Cellular and Molecular Biology, 2017)
In this study, in vitro maturation was performed in presence of various concentrations (0, 10, 100, or 1000 µM) of H2O2. The intracellular glutathione (GSH) level, fertilization, cleavage, and blastocyst rates, total cell number, and apoptotic cell number and expression of Bax, Bcl-2, and p53 genes in blastocyst-stage embryos were studied. At 10 Î¼M H2O2 concentration, a higher GSH level was detected in comparison to the other groups while oocytes exposed to 1000 Î¼M H2O2 had the lowest GSH level. Treatment of oocytes with 1000 Î¼M H2O2 decreased the rate of two pronuclei formation as compared with other groups. A higher rate of blastocyst formation was seen in 100 Î¼M H2O2 group as compared with the control group. However, exogenous H2O2 in maturation medium did not affect total cell numbers and apoptotic cell ratio at the blastocyst stage. Moreover, mRNA transcript abundance of Bax, Bcl-2, and p53 genes was similar between blastocysts derived from H2O2-induced oocytes and control blastocysts. Treatment of oocytes with H2O2 at mild level during in vitro maturation had a positive effect on GSH level and this, in turn, may lead to improvement in preimplantation embryonic development.